Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogea L) Terhadap Kasgot dan Pupuk TSP Pada Tanah Ultisol - Lubis, Andri Sarkoni; Panggabean, Ellen Lumisar (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Peanuts (Arachis hypogaea L.) are agricultural commodities with high nutritional value and potential productivity. Fertilization plays an important role in supporting plant growth and yield, both through organic and inorganic fertilizers. This study aims to determine the effect of the application of kasgot and TSP fertilizers on the growth and yield of peanuts in ultisol soil. The study used a factorial 4×4 Random Group Design (RAK), with four levels of kasgot fertilizer (0, 0.5, 1, and 1.5 kg/polybag) and four levels of TSP fertilizer (0, 7.8, 15, and 22.5 g/polybag), as well as three replicates. The results showed that kasgot treatment had a significant effect on the number of pods per plot, but not significantly on the height of the plant, the number of pods per sample, and the weight of the pods. Meanwhile, TSP fertilizer has a noticeable effect on plant height, but not significantly on other yield parameters. These findings demonstrate the importance of appropriate fertilization strategies to increase peanut productivity in ultisol soils.